MEDIA PEMBELAJARAN UNTUK PEMBELAJARAN ONLINE DI MASA PANDEMI COVID 19 - Husna Lubis; Riskyka; Joko Pribadi (LPPM STKIP AL MAKSUM, 2022)
The emergence of the Covid-19 pandemic has hampered several sectors in Indonesia, in this case education. The government has imposed restrictions on community activities to prevent crowds to prevent the spread of the COVID-19 virus. The government has also shifted teaching and learning activities from conventional or face-to-face to online or online classes. Of course this has an impact on the unfamiliarity of educators and students in carrying out learning, because they have to use online learning media. Various types of online learning media have emerged. Some of them are whatsapp, google classroom, online class, zoom meeting, google meet, learning video, quizziz, facbook, e-learning and others. The purpose of this study is to describe the use of interesting learning media and can support and facilitate online learning. For student. The results of this writing study are several learning media that can support learning and learning activities, namely learning videos, quizziz, and facebook because they are easy to access and do not require too many quotas, thus burdening students. However, during online learning, students' space for movement is limited and cannot play with their peers. This causes students to feel bored, bored and sometimes less enthusiastic. Therefore, teachers must know the condition of students and be able to motivate students to be enthusiastic about online learning.